Andrés Caicedo: suicidio y consagración - Van der Huck, Felipe (Sociedad y Economía, 2004)
The paper studies the links between literary consecration and suicide, focusing in the cas e study of the Colombian writer Andres Caicedo. The idea, above ll, is to describe and analyze how the process of literary consecration in this case has been produced in relation to an emblematic “fact”: his suicide. The paper has three parts. The first one shows how Caicedo’s life has been transformed into a waiting of death, necessary and calculated at the same time. In the second one, a study is made of how this life organized as fate assumes a sense that is manifested in each one of its “events”. The final part criticizes the most common ideas about Andres Caicedo´s suicide, showing that this decision was not an unequivocal token.